Enhancing Motivation for Overcoming Learning and Behavior Problems. - Adelman, Howard S.; Taylor, Linda (Journal of Learning Disabilities)
Discusses the value of current motivational theories in developing guidelines for assessing learning disabilities and behavioral problems among students. Development of frameworks and procedures for correcting motivational problems; Suggestion of times when correction of motivational problems is necessary.